Caracterización hacia un plan de gestión de residuos sólidos domiciliarios en la zona urbana del distrito de Iquitos-2019 - Gonzáles Shapiama, Carmen del Pilar (2024)
The rehearsal was in Iquitos, the objective was to carry out a characterization of solid spoils, to develop a Plan of Administration, the investigation was quantitative, I not design experimental, the population conformed it all the housings Moore she remains silent from the 1era block until the last, total 3 423 housings, the sample was 84, it was used as technique the survey, before its application he/she was carried out a test pilot of 10% giving him the validation the Alpha of Cronbach, to process the results the Software it was used Infostat and the SPSS V24, calculation leaf Excel, being reached the conclusions: the age had bigger representativeness in a range from 49 to 59 years with (33.3%), in sex the feminine one (78.6%), people's that inhabit a housing 4 number (35.7%), the (100%) they have basic services, the one deposits used it is the plastic bag (66.6%), a week they take out its residuals 3 times (73.8%), the (66.7%) it doesn't classify its garbage and alone they carry out it the (33.3%), the (52.4%) reutilizing plastic bottles, and the (100%) they receive municipal toilet, on the Municipal work the (66.7%) he/she says to be to regulate and the (33.3%) he/she says that it is good, the (100%) they pay wills, the (100%) they say that an inadequate handling of these residuals results in problems to the health, the biggest percentage of residuals is the organic ones (68%) which can be used for the compost elaboration and being used as fertilizers in cultivations.